Hubungan Dukungan Sosial dengan Academic Burnout Pada Mahasiswa Keperawatan - Selvy Saputri Damayanti; Retno Issriviatiningrum; Muh.Abdurrouf (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
Academic burnout is prone to occur in students who experience Fatigue because they feel pressured by lectures and feel incompetent as students. Fatigue that is felt if it is not immediately overcome and continues, it can decrease academic achievement and even disrupt mental and physical health. To overcome or prevent burnout, students need social support from family, friends and significant other support. The goal was to analyze the relationship between social support and academic burnout in Unissula nursing students. This study applies a quantitative method with a cross sectional approach and data is obtained through the distribution of MSPSS (Multidimensional Scale of Perceived Social Support) questionnaire consisting of 18 statements and MBI-SS (Maslach Burnout Inventory-Student Survey) consisting of 19 statements, with a total of 141 respondents who were randomly selected without looking at certain characteristics using a simple technique random sampling. The results of this study show that the most social support is in the low category with 102 (72.3%) students while the most academic burnout is in the medium category with 120 (85.1%) students. The results of the statistical test obtained a p-value of 0.000 with a closeness of -0.402 which means that there is a relationship between social support and academic burnout with moderate closeness. There was a meaningful relationship between Social Support and Academic Burnout of FIK Unissula students with p value (0.000) < ɑ (0.05).